1996
DOI: 10.1128/jvi.70.2.1050-1060.1996
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase A and the serine-rich region of herpes simplex virus type 1 ICP4 in viral replication

Abstract: Efficient expression of herpes simplex virus genes requires the synthesis of functional ICP4, a nuclear phosphoprotein that contains a prominent serine-rich region between amino acids 142 and 210. Residues in this region not only are potential sites for phosphorylation but also are involved in the functions of ICP4. By comparing the growth of a virus in which this region is deleted (d8-10) with wild-type virus (KOS) in PC12 cells or PC12 cells that are deficient in cyclic AMP-dependent protein kinase (PKA), tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 66 publications
(101 reference statements)
2
30
0
Order By: Relevance
“…In addition, the E1a, E3 and E4 promoters of Ad contain CREs (Leza and Hearing, 1989; Meyer et al ., 1993). In HSV, ICP4 is a substrate for PKA and its phosphorylation promotes HSV lytic replication (Xia et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the E1a, E3 and E4 promoters of Ad contain CREs (Leza and Hearing, 1989; Meyer et al ., 1993). In HSV, ICP4 is a substrate for PKA and its phosphorylation promotes HSV lytic replication (Xia et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have not tested the ability of these mutants to support the growth of an ICP27-null mutant virus in cells of neuronal origin. Recently, it has been shown that deletion of a highly conserved polyserine tract found between residues 184 and 198 in HSV-1 ICP4 results in a virus that is marginally impaired for growth in culture and in the eyes of infected mice but is completely impaired for growth in the trigeminal ganglia (2,53). To address questions on specific functions and interactions of ICP27 during viral infection, the kinase consensus site mutations are being introduced into the viral genome by marker transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about which cellular kinases phosphorylate ICP27 in vivo. However, kinases such as PKA, CKII, and PKC have been implicated in HSV-1 replication (53). Furthermore, there are good consensus sites for PKA, CKII, and PKC phosphorylation in the predicted peptide sequence of ICP27.…”
Section: Figmentioning
confidence: 99%
“…The goal of this study was to analyze the replication of an ICP27-null (44) recombinant HSV-1 strain (vBS⌬27) in cultured human cells. Initially, we were interested in directly comparing the cytopathic effects of the ICP27-null virus replication in human cells with that in Vero cells, since some mutant viruses, especially those carrying mutations in genes encoding IE proteins (3,42,47), were shown to have phenotypes which varied with the type of cell line or tissue used for the infections. Monolayer cultures of either Vero and Vero 2.2 (nonhuman) or 143tk Ϫ , HEp-2, and HeLa (human) cells were mock infected or infected with vBS⌬27, KOS1.1, or vBS⌬27R as described in Materials and Methods.…”
Section: Differing Morphologies Of Vbs⌬27-infected Cell Monolayersmentioning
confidence: 99%